COMPARISON OF ADVERSE FETOMATERNAL OUTCOME IN EARLY AND LATE ONSET PRE ECLAMPSIA - Gohar, Samina; Syed, Wajeeha (Journal of Postgraduate Medical Institute, 2021)
Objective: To compare adverse feto-maternal outcome between women with early and late onset preeclampsia. Methodology: This cross sectional study was conducted in Gynecology and Obstetrics and Gynecology Department, Lady Reading Hospital, Peshawar from March 2016 to September 2016. A total of 254 patients having singleton pregnancy of more than 20 weeks were included. Week 34 was used as a cutoff to classify patients into Early Onset Preeclampsia (EOPE) and Late Onset Preeclampsia (LOPE). All the subjects were followed up till one week after delivery to compare adverse fetomaternal outcome. SPSS version 25 was used for data analysis. Results: Out of 254 patients, 172 (67.7%) patients had LOPE while 82 (32.3%) presented with EOPE. The mean Body Mass Index (BMI) for EOPE and LOPE was 25.25±1.70kg/m2 and 25.97±2.03kg/m2, respectively. Most of the patients were multigravida in both groups, 43 (52.4%) in EOPE and 122 (70.93%) in LOPE. Preterm birth was more common in the EOPE (n=49, 59.75%) as compared to LOPE (n=60, 34.88%) with a p-value of 0.0001. LOPE group had more cesarean sections (n=62, 36.02%) than EOPE (n=16, 19.53%) with a p-value of 0.008. Neonatal Intensive Care Unit (NICU) admissions were more common in EOPE group (60.92%) as compared to LOPE (41.82%) having a p-value of 0.004. Neonatal deaths and small for gestational age was found to be insignificant in the two groups. Conclusion: Preterm birth and NICU admissions were more common in EOPE while cesarean section was more commonly done in LOPE.